Impact of malnutrition and frailty on mortality and major amputation in patients with CLTI. Issue 4 (3rd February 2022) - Karim, Adham M.; Li, Jun; Panhwar, Muhammad S.; Arshad, Samiullah; Shalabi, Shihabaldean; Mena‐Hurtado, Carlos; Aronow, Herbert D.; Secemsky, Eric A.; Shishehbor, Mehdi H.
Abstract: Objectives: To understand the prevalence of malnutrition and its association with chronic limb‐threatening ischemia (CLTI) outcomes; to clarify the differential impact of revascularization methods on outcomes; to assess the ability of the CLTI Frailty Risk Score (CLTI‐FRS) to predict adverse events in patients hospitalized with CLTI. Background: Despite advances in the management of CLTI, a majority still undergo major amputation, and a minority heal within 6 months. There is a lack of validated assessment tools for the identification and management of frailty and malnutrition in these patients. Methods: Using the National Inpatient Sample from January 2012 to September 2015, we identified all patients with CLTI using International Classification of Diseases Ninth Edition Clinical Modification codes. The cohort was divided into three groups according to nutritional status. Multivariable regression analysis was used to analyze the interaction between malnutrition and outcomes of interest. Results: Of 1, 414, 080 CLTI‐related hospitalizations, 163, 835 (11.6%) were malnourished, 332, 855 (23.5%) patients were frail, 917, 390 (64.9%) were well‐nourished. In‐hospital mortality, major amputation, the average length of stay, and hospital costs were highest among malnourished or frail patients and lowest in well‐nourished patients ( p  < 0.001). Malnourished and frail patients were observed to have lower rates of mortality with endovascular revascularization as compared to surgical (adjusted odds ratios: 0.675 [0.533–0.854; p  = 0.001]). Conclusion: Many patients with CLTI are malnourished or frail, and this is associated with mortality and amputation. Both malnourished and frail patients were observed to have a mortality benefit with a less invasive approach to revascularization. Better assessment of nutritional and frailty status of CLTI patients may guide therapy and help prevent amputation and death.